Identifikasi Saham Undervalued Sektor Makanan dan Minuman Berbasis PER dan PBV (BEI 2021–2025) - Rani Selfia Sipayung; Dhea Yurike Silaban; Ruhama Girsang; Putri Kemala Dewi Lubis (CV. ALIM'SPUBLISHING, 2026)
Shares trading below their intrinsic value present compelling return opportunities, particularly for long‑term investors. This study aims to assess the valuation of eight food‑and‑beverage issuers listed on the Indonesia Stock Exchange (IDX) over the 2021–2025 period using two market‑based valuation instruments: the Price to Earnings Ratio (PER) and the Price to Book Value (PBV). A quantitative descriptive design was employed, and a purposive sampling technique selected eight issuers: INDF, ICBP, MYOR, ROTI, GOOD, CLEO, CMRY, and CAMP. The sectoral benchmarks obtained were an average industry PER of 22.64 times and an average industry PBV of 3.45 times. Comparative analysis reveals that INDF (PER 7.38x; PBV 0.59x), ICBP (PER 17.60x; PBV 1.83x), ROTI (PER 18.86x; PBV 2.47x), and CAMP (PER 16.59x; PBV 1.78x) are undervalued relative to the industry average and therefore merit consideration as buy candidates, while MYOR, GOOD, CLEO, and CMRY are overvalued. INDF emerges as the most attractive investment candidate because its PBV remained consistently below 1.00 throughout the observation window, a condition recognized in value‑investing literature as deeply undervalued. The findings reinforce the argument that combining PER and PBV serves as a reliable tool for identifying high‑potential stocks from a fundamental analysis perspective.